Technology pooling licensing agreements: promoting patent access through collaborative IP mechanisms (2010)
Patent pools are essentially agreements where different patent holders “pool” together, i.e. assemble, their respective technologies in order to license them as a unique “package” to third parties.1 Nowadays, in response to the globalisation of technologies and more severe conditions of competition, resulting in a faster pace of innovation also at an international level, technology pools have increasingly gained relevance as successful cooperative IP licensing models.2 Reflecting the importance won by such practices, the purpose of this contribution is to outline the defining features and the strategic considerations underlying the establishment of patent pools, both in a legal and empirical context, in order to identify the best conditions for such cooperative practices to prosper in a competitive setting, with a view to cultivating innovation. In this respect, attention will be brought both to the internal organizational framework adopted, with regard to the particular nature of the technologies involved, and on the legislative treatment that patent pools have been reserved in different jurisdictions, with particular attention to the EU and US systems,3 in a global perspective. In fact, there are many questions still to be answered, and correspondingly many new fields of application in which the successful implementation of patent pools still needs to be explored. However, within the scope of this research project, the present contribution hopes to shed at least some light on and raise interest in such collaborative IP mechanisms and their goal to promote technology access.